KARAKTER ENTREPRENEUR DALAM ISLAM - Muhammad Nur Adnan Saputra (STAI Syubbanul Wathon Magelang, 2021)
There are still many Muslims who are weak in control of the economy and very high economic dependence on other parties as well as improper economic activity which indicates the need to develop an entrepreneurial mentality based on Islamic teachings. This research uses the literature research method, this article uses literature in the form of books, relevant journals, and scientific papers. The results of the research are related to entrepreneurship, Muslims can utilize all their potential for entrepreneurship. Everything that is done requires effort and hard work to get it as well as seeking sustenance, it takes effort to get it. Muslims can equip themselves with entrepreneurial skills and must have a moral foundation because doing business is two things that run simultaneously. For Muslims, it is not recommended to be extravagant, squander wealth, and exaggerate.